Aspects of renormalisation in some quantum field theories - Roy, Alan A (Rhodes University, Faculty of Science, Department of Mathematics, 1998)
Renormalisation is an important aspect of Quantum Field Theory. It is used to create physically meaningful theories and some major developments took place in the 1970's and onwards. We consider Renormalisation in its application to the theories of Ïˆâ ´ , Quantum Electrodynamics, Quantum Chromodynamics and the Background Field Method. Feynman diagrams are used to illustrate many of the concepts.
Keywords: Quantum field theory; Renormalization group